Heroes in Lithuania: Aspect of (De-)Heroization, Case, Approach - Sviderskytė, Gražina Kristina (Lietuvos istorijos studijos, 2019)
In this article, I explore a tendency of (de-)heroization in Lithuania during the 20th century. This research is focused on a historical hero, that is, a mental construct based on a historical prototype: a protagonist of the factual versus fictional narrative who was idealized, mythologized, and initiated to meet the current collective needs and demands. The aim can be generalized by the following questions: who is a historical hero and why is he important; what makes (de-)heroization relevant and how did/does it occur; why this phenomenon is relevant to Lithuania and how should it be further explored? The applied methodology involved a case study (an analysis of the transforming and transfigured heroes, the origin and evolution of the heroic narrative about Lithuanian-American pilots Stephen William Darius and Stanley [Thomas] Girch, aka Darius and Girėnas), a discourse analysis, and an interdisciplinary approach focusing on the heroism humanities in the context of the emerging transdisciplinary heroism science. The emergence and specificity of the heroic ideals – the Great Lithuanian and Winged Lithuanian – and types – the Warrior and Aviator – is explored, and the tendency of idealization and ideologization as well as inertia and stagnation in heroization processes are revealed. The resilience of the cult of power, as well as ideological relics of Lithuanian nationalism and even Soviet utopianism in the current heroism discourse, has led to an unsettling conclusion that the process of hero-making simultaneously and repeatedly involved an exalted idealization and deep depreciation of the heroic figures and their original ideas and/or achievements and of the historical past and historical heritage in general. This kind of (de-)heroization was an integral part of the construction of the Lithuanian mythical modernity.